Epilepsy in children or sexual health in adolescents – critical review - Gray, Nicola (2010)
Abstract This dissertation reviews the impact of epilepsy during adolescence. To do this, it discusses typical adolescent behaviours and traits in five specific areas and then identifies the impact that epilepsy may have upon those. The areas covered are acceptance, independence, adolescent lifestyle, intimate relationships and physiological factors. A wide range of topics related to these issues are discussed and include such things as identity, social stigma, parental overprotection, disclosure, alcohol and drugs, driving, relationship development, contraception, pregnancy, exercise and physiological brain development. This range of both psychological and practical issues allows an integrated discussion of all areas both informing and advising healthcare professionals. As a result of this study, it is clear that all areas of adolescence are heavily linked with multiple related themes with a central issue of parental overprotection running throughout. The experiences of adolescence are different for all, epileptic or not. However, there are still common stumbling blocks for adolescents with epilepsy which is why the topics noted above have been explored. Technology and the family are identified as areas for future research and development as they may hold interesting points that are yet to be recognised or yet to be introduced to general practice.